(untitled) (Research, Society and Development, 2022)
The Brazilian semiarid region goes through recurrent scenarios of the triple epidemics of arboviruses (Dengue, Zika and Chikungunya), transmitted by Aedes aegypti, with an incidence of diseases and their sequelae in human health. There is, therefore, an increase in risks, with the multifactorial determination of arboviruses through the interrelation of ecological, political, economic and social factors. In addition to the changes in the social fabric, resulting from the deficient urbanization system and the inconsistency in the basic sanitation infrastructure, intermittent piped water supply leading to the accumulation of water in an inappropriate place, which favors the proliferation of vectors and other diseases, in addition to vulnerabilities environmental. The methodology applied, depending on the objective of the study, is of a descriptive-exploratory nature, with a qualitative approach, through the application of semi-structured interviews applied with social actors from the infrastructure/city hall and population of the areas with the highest incidence of arboviruses, in the municipalities of Olivedos, Juazeirinho and Tenório in Paraíba. The final considerations point to the decision-making of the State in the adoption of public policies for the prevention and control of arboviruses, increase in the production of scientific knowledge with analysis focused on learning the process of investigation of the disease and its sequels, increase of resources destined to research for epidemiological investigation and implementation of new technologies, in addition to expanding environmental education, with dynamic and permanent mechanisms to combat the vector.